2020
DOI: 10.13058/raep.2020.v21n3.1787
|View full text |Cite
|
Sign up to set email alerts
|

Business Games and Stock Market: An analysis of students’ learning in a Business Administration course

Abstract: This paper addresses the use of experiential learning to improve knowledge about the capital market, by applying a program with business games, using an electronic simulator of the Brazilian stock market. The objective was analyzing the cognitive domain of the participants after application of an educational program about the capital market, using a business game tailored for stock market trading. The descriptive study, with a quantitative approach, used the quasi-experiment technique to collect data on the le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…The paper on simulation games used in operations management concluded that simulation tools were more effective than traditional teaching methods for developing higher-order decision-making skills required for dealing with complex problems in operations management (Pasin & Giroux, 2011). Finally, Oliveira and Melo's (2020) study of the use of an electronic simulation of the Brazilian stock market found that this approach delivered significant benefits to student acquisition of skills and knowledge related to stock trading in capital markets.…”
Section: Business-level 1 Clustermentioning
confidence: 99%
“…The paper on simulation games used in operations management concluded that simulation tools were more effective than traditional teaching methods for developing higher-order decision-making skills required for dealing with complex problems in operations management (Pasin & Giroux, 2011). Finally, Oliveira and Melo's (2020) study of the use of an electronic simulation of the Brazilian stock market found that this approach delivered significant benefits to student acquisition of skills and knowledge related to stock trading in capital markets.…”
Section: Business-level 1 Clustermentioning
confidence: 99%
“…According to Abbas & Andras (2017) research, entrepreneurship instruction can boost students' perceived entrepreneurial selfefficacy and perceived desirability for launching new businesses, which in turn can boost their entrepreneurial intentions for starting new businesses. Oliveira & Melo, (2020) experiential learning techniques like serious business games can raise students' awareness of their need for further education as well as the challenges of entrepreneurship and business management. Overall, the papers suggest that SSP can have an impact on EV creation in universities by giving students the skills and resources they need to launch their businesses.…”
Section: Question One: How Student-staff Partnership (Ssp) Influence ...mentioning
confidence: 99%